Development of the germinal epithelium and early folliculogenesis during ovarian morphogenesis in the cichlid fish Cichlasoma dimerus (Teleostei, Perciformes) - Meijide, Fernando Javier (2014)
Formation of the germinal epithelium and folliculogenesis during ovarian development in Cichlasoma dimerus were described at the light- and electron-microscopic levels. Prior to gonadal differentiation, germ cells and enveloping support cells reside within an inpocketing of the coelomic epithelium. Separation of the germinal and interstitial compartments of the gonad by a basement membrane is apparent from early gonadal development. Upon ovarian differentiation, oogonia undergo cyst-forming divisions leading to the formation of clusters of interconnected cystocytes that synchronously enter meiosis, becoming oocytes. At the pachytene step, each oocyte becomes individualized by cytoplasmic extensions of prefollicle cells, thereby developing as an ovarian follicle. Subsequent somatic reorganization leads to the formation of the ovarian lumen in a cephalo-caudal gradient. As a result, the germinal epithelium becomes internalized and lines the ovarian lumen. As defined by its origin from the germinal epithelium, the ovarian follicle is composed of an oocyte and the surrounding follicle cells. Thecal cells derived from the stroma encompass the basement membrane outside the follicle, thus forming a follicle complex. A common basement membrane is shared by the germinal epithelium and the follicle complex along a small portion of its surface. This point of attachment represents the site at which the oocyte would be released to the ovarian lumen during ovulation.